Mental health and its strict relationship with the Iraqi rulers' decision to boxing - abd Al-Munaem,Sanaria Jabbar Alsaadi, Firas; Kamel Shallan, Eyad (International Journal of Psychosocial Rehabilitation, 2020)
The significant development that taking place in the level of sports competitions in various games has been accompanied by a significant increase in the pressures of experienced referees sports competitions as well as pressures of various public and private life outside and the competition facing and naturally requires that referee be at a high level of mental health and fitness Physical and functional, and the problem of the current research lies in the weakness in the ability of boxing referees to make decisions due to the low level of mental health, so the researchers decided to develop appropriate solutions to the problem suffered by the referees and overcome the lapses that they may fall into during fights in order to raise them to the highest levels. The current study aims to identify the mental health of advanced boxing referees in Iraq, to identify the accuracy of decision-making among advanced boxing referees in Iraq, and to identify the relationship between mental health and decision-making among advanced boxing referees in Iraq. The research community is one of the referees of the boxing game for Iraqi clubs and the sample was selected in the random manner of the sports season (2020-2021); the total research community (180) referees and the research sample of (100) was selected as the judge of the main trial procedures and their percentage (55.55%), and (15) were selected for the survey experiment and the percentage problem was (8.33%)